2021
DOI: 10.3390/biomedicines9111522
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of a Concoction of Natural Bioactive Compounds—Mechanistic Insights

Abstract: Natural bioactive compounds derived from plant-based products are known for their biological immunomodulatory activities. They possess systemic pleiotropic effects, minimal side effects, and very low toxicities. Plant-based bioactive compounds have tremendous potential as natural therapeutic entities against various disease conditions and act as anti-inflammatory, antioxidant, anti-mutagenic, anti-microbial, anti-viral, anti-tumour, anti-allergic, neuroprotective, and cardioprotective agents. A herbal formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 45 publications
(122 reference statements)
0
26
0
Order By: Relevance
“…Based on CT network, we found that FLKM principally regulates inflammatory through resveratrol, stigmasterol, beta-sitosterol, sesamin, and quercetin as well as other components. Studies have found that they can regulate various inflammatory factors and pathways to exert anti-inflammatory properties ( Zhong et al, 2012 ; Lopes Pinheiro et al, 2019 ; Ahmad Khan et al, 2020 ; Gangwar et al, 2021 ). Among them, stigmasterol, one of a phytosterols, is found in a number of medicinal plants.…”
Section: Discussionmentioning
confidence: 99%
“…Based on CT network, we found that FLKM principally regulates inflammatory through resveratrol, stigmasterol, beta-sitosterol, sesamin, and quercetin as well as other components. Studies have found that they can regulate various inflammatory factors and pathways to exert anti-inflammatory properties ( Zhong et al, 2012 ; Lopes Pinheiro et al, 2019 ; Ahmad Khan et al, 2020 ; Gangwar et al, 2021 ). Among them, stigmasterol, one of a phytosterols, is found in a number of medicinal plants.…”
Section: Discussionmentioning
confidence: 99%
“…Through the IL-17 signaling pathway, γδT cells that can produce IL-17 are shown to control neutrophil influx under infection [ 58 ]. Treg cells secrete CXCL8 and promote neutrophil recruitment through CXCL8 [ 59 ]. The characteristics of Yersinia lung infection are severe pulmonary inflammation and a high abundance of neutrophil infiltration [ 60 ] because of the Yersinia infection pathway, there is a great risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear factor kappa-B (NF-κB) signal transduction mechanism is involved in the progression of multiple cancers ( 82 ) and is essential for maintaining cell health by controlling fundamental cellular processes such as cell differentiation, growth, and survival ( 83 ). A recent study indicated that SIT positively modulates the NF-κB signaling pathway ( 84 ). Ziyuan et al.…”
Section: Effect Of Sit On Other Factors Affecting Tumor Growthmentioning
confidence: 99%